REVOLUTIONIZING ECTOPROSTHETICS IN PATIENTS WITH METACHRONIC AURICULAR TUMORS VIA 5D DIGITAL DESIGN - Kambarova Shakhnoza Alixuseynovna (KONFERENSIYALAR, 2025)
Annotation:Aesthetic, functional, and psychological illnesses are caused by defects of the craniofacial region of different etiologies, and these disorders are frequently  only  treated  surgically  using  a  variety  of  excision  techniques. Regretfully, not all instances can be resolved surgically in terms of satisfactory cosmetic  results  or  reconstructive  treatments.  Sometimes  patients  refuse  major, multi-stage  surgeries  because  of  fear.  Facial  prosthesis  is  an  alternate  therapy option  for  patients  in  the  scenarios  mentioned.  When  manufacturing ectoprostheses, outstanding aesthetic outcomes are achievable because to modern silicone materials. These devices can be attached using medical adhesives, or the prosthesis can stick to the skin better thanks to the funnel-shaped structure.